2018
DOI: 10.1002/jcc.25175
|View full text |Cite
|
Sign up to set email alerts
|

FALDI‐based decomposition of an atomic interaction line leads to 3D representation of the multicenter nature of interactions

Abstract: Atomic interaction lines (AILs) and the QTAIM's molecular graphs provide a predominantly two-center viewpoint of interatomic interactions. While such a bicentric interpretation is sufficient for most covalent bonds, it fails to adequately describe both formal multicenter bonds as well as many non-covalent interactions with some multicenter character. We present an extension to our Fragment, Atomic, Localized, Delocalized and Interatomic (FALDI) electron density (ED) decomposition scheme, with which we can meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…We recently introduced the FALDI ED decomposition scheme . FALDI uses concepts from the domain averaged Fermi hole (DAFH) approach to calculate pseudo‐second‐order contributions arising from electrons within QTAIM‐defined atomic basins.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently introduced the FALDI ED decomposition scheme . FALDI uses concepts from the domain averaged Fermi hole (DAFH) approach to calculate pseudo‐second‐order contributions arising from electrons within QTAIM‐defined atomic basins.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the ED (as well as critical points in the ED) is a field influenced by all particles of a molecule, and, therefore, the notion that a DB is a diatomic property is false. In fact, we have previously shown that the ED at a (3,–1) CP is a result of contributions from delocalized electrons arising from multiple atoms, thereby concluding that a DB is inherently multicenter in nature even in the case of a classical covalent bond. A similar problem facing existing interpretations of a DB is the use of the second eigenvalue of the Hessian matrix as a measure of electron concentration for the fulfillment of Feynman's theorem (the basis for Bader's interpretation as well as the interpretation of other methods such as NCI).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations